The 2nd IEEE Conference on Power Engineering and Renewable Energy (ICPERE) 2014 2014
DOI: 10.1109/icpere.2014.7067206
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of partial discharge characteristics and dissolved gas analysis on palm-based oil as insulating material

Abstract: Partial discharge (PD) properties and dissolved gas analysis (DGA) are investigated on two kinds of fatty acid alkyl esters synthesized from palm oil with additive, namely Pastell 2H-08 and Palm Fatty Acid Ester (PFAE) to be adopted in power transformers. For comparison, the properties of mineral oil which is commercially used transformer oil were also investigated in the research works. The results revealed that PD repetition rate number of the ester oils with additive increase remarkably at above 15 kV rms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…1, June 2022: 45-58 Table 5. Properties value of vegetative oil [9], [14], [16], [28], [29], [30], [31], [32], [33], [34].…”
Section: Ahp System Develop Using Microsoft Excelmentioning
confidence: 99%
“…1, June 2022: 45-58 Table 5. Properties value of vegetative oil [9], [14], [16], [28], [29], [30], [31], [32], [33], [34].…”
Section: Ahp System Develop Using Microsoft Excelmentioning
confidence: 99%
“…The equations of Bio Electra TM and Bio Temp TM were found and expected to be similar since both natural esters derived from sunflower seeds. Achmad Susilo et al [23] investigated partial discharge characteristics and dissolved gas analysis of two types of fatty acid alkyl esters -Pastell 2H-08 and palm fatty acid ester (PFAE) and compared with mineral oil. It was reported that partial discharge of Pastell 2H-08 increased above 15 kV rms than that of mineral oil due to higher dissipation factor.…”
Section: Types Of Transformer Oil: Mineral Vegetable or Blend Oilmentioning
confidence: 99%